The association of eating pattern and grocery shopping practices among adult consumers at supermarket Puncak Alam, Selangor / Maziana Mat Zin - Mat Zin, Maziana (2016)
The eating pattern changes among consumers had been associated with the grocery shopping practices. High consumption of sugar, saturated fat and salt led to poor diet due to the availability of major products in the market in which high in calories, refined carbohydrates, fat and sodium. Besides, the socioeconomic status influenced their behaviors toward grocery shopping practices as well as patterning the quality of the eating patte,.m. The aims ofthis study are to determine the association ofeating pattern and grocery shopping practices among supermarket adult consumers, to determine the eating pattern among supermarket adult consumers and to determine the risk factors that affect the grocery shopping practices among supermarket adult consumers. A total of 118 consumers between aged 20 to 64 years old and consumers who volunteered and free from any physical disability were studied. A cross sectional study was conducted in urban area at supermarket in Puncak Alam from September until November 2015. There was a poor positive (r = 0.233) and significant (p<0.05) correlation between eating pattern and grocery shopping practices. Consumers that practiced recommended grocery shopping had better fruit serving per day (1.3 ± 0.96) with p = 0.004. Vegetables serving per day slightly higher in recommended shopping practices (1.4 ± 0.6) with p = 0.025. There were higher prevalence of secondary educational level (51.4%) and household income that less than RM 2300 (47.7%) among those with poor eating pattern. Secondary educational level had crude Odd Ratio [cOR]): 0.43; 95% Confidence Interval: 0.19,0.99), household income less than RM 2300 (cOR: 0.34; 95% CI: 0.15,0.75) and money spent per shopping less than RM 100 (cOR: 0.44; 95% CI: 0.21, 0.95) were the associated risk factors that affect grocery shopping practices. This is important in targeting the group of poor eating pattern that practiced regular grocery shopping with risk factors that can develop any diet related disease. Keywords: Eating pattern, grocery shopping practices, socioeconomic status, health